2017
DOI: 10.1002/ccd.27442
|View full text |Cite
|
Sign up to set email alerts
|

Septal reduction therapy using nonalcohol agent in hypertrophic obstructive cardiomyopathy: Single center experience

Abstract: In conclusion, our small-sized preliminary study results showed that septal reduction therapy using EVOH is an effective alternative option in reducing symptoms and LVOT gradient in HOCM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…4,8,[19][20][21] Due to the high frequency of procedure-related complications with ASA, a need exists for percutaneous ablation techniques with alternative septal embolization agents. 15 The most common conduction system problem after ASA is the development of RBBB, and studies showed that RBBB does not affect prognosis. 22 Researchers even showed that the development of RBBB may be correlated with the necrotic area's size and the procedure's success.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4,8,[19][20][21] Due to the high frequency of procedure-related complications with ASA, a need exists for percutaneous ablation techniques with alternative septal embolization agents. 15 The most common conduction system problem after ASA is the development of RBBB, and studies showed that RBBB does not affect prognosis. 22 Researchers even showed that the development of RBBB may be correlated with the necrotic area's size and the procedure's success.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the nonadhesive property of EVOH, the filling of the septal artery was checked under fluoroscopy or angiography during its injection. After the occlusion of the septal artery, the microcatheter, and the whole system were withdrawn together 15 (Figure 2).…”
Section: Evoh-dmso Septal Ablation Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Koljaja-Batzner et al, previously published a case report on the treatment of a female patient in her sixties with ASA, who was hospitalized for 9 months and had no problems [ 40 - 44 ]. Asil et al, verified no mortality throughout the 12-month follow-up period [ 44 ].…”
Section: Alcohol Septal Ablationmentioning
confidence: 99%
“…Koljaja-Batzner et al, previously published a case report on the treatment of a female patient in her sixties with ASA, who was hospitalized for 9 months and had no problems [ 40 - 44 ]. Asil et al, verified no mortality throughout the 12-month follow-up period [ 44 ]. Bytyçi et al confirmed their findings, indicating that periprocedural issues were less common with alcohol ablation, even though reintervention and pacemaker implants were more common therein [ 42 - 44 ].…”
Section: Alcohol Septal Ablationmentioning
confidence: 99%